2015
DOI: 10.1073/pnas.1502295112
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of fear extinction by novelty depends on dopamine acting on D1-subtype dopamine receptors in hippocampus

Abstract: Extinction is the learned inhibition of retrieval. Recently it was shown that a brief exposure to a novel environment enhances the extinction of contextual fear in rats, an effect explainable by a synaptic tagging-and-capture process. Here we examine whether this also happens with the extinction of another fear-motivated task, inhibitory avoidance (IA), and whether it depends on dopamine acting on D1 or D5 receptors. Rats were trained first in IA and then in extinction of this task. The retention of extinction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 50 publications
2
41
0
Order By: Relevance
“…The distinct patterns of PKA vs PLC coupled D1/5 receptor expression (Nishi et al, 2011) might indicate that SKF 83822 (PKA-coupled D1/5R agonist) may specifically engage the cortical networks involved in fear extinction through activation of PKA-coupled D1/5 receptors, whereas SKF 83959 may primarily activate the amygdala and hippocampus without affecting fear extinction. Our studies are also in concordance with Menezes et al (2015), who demonstrated that novelty-induced enhancement of fear extinction is mediated via D1/5 receptor activation and PKA signaling.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The distinct patterns of PKA vs PLC coupled D1/5 receptor expression (Nishi et al, 2011) might indicate that SKF 83822 (PKA-coupled D1/5R agonist) may specifically engage the cortical networks involved in fear extinction through activation of PKA-coupled D1/5 receptors, whereas SKF 83959 may primarily activate the amygdala and hippocampus without affecting fear extinction. Our studies are also in concordance with Menezes et al (2015), who demonstrated that novelty-induced enhancement of fear extinction is mediated via D1/5 receptor activation and PKA signaling.…”
Section: Discussionsupporting
confidence: 92%
“…Most of the pharmacological and behavioral evidence for a role of D1/5 receptors in aversive memory comes from studies with D1/5 receptor antagonists (Menezes et al, 2015;Holtzman-Assif et al, 2010). Fewer studies have examined whether activating D1/5 receptors could promote memory and extinction, although studies with the partial agonist SKF 38393 have demonstrated both enhancements (Fiorenza et al, 2012;Rey et al, 2014) and impairments of fear extinction retention (Borowski and Kokkinidis, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…69 The VTA, which is the seat of dopaminergic cell bodies of the mesocorticolimbic dopamine system, has connections to and from the hippocampus and has been associated with facilitation of fear extinction. 70 Disturbances in this pathway have been linked to enhanced fear generalization in clinical samples. 71 One implication from these studies is that dopamine-associated hippocampal function is critical for the encoding of distinct memory representations.…”
Section: Discussionmentioning
confidence: 99%
“…Two basic variants of IA are used in rats or mice: the stepdown model, in which rodents receive a footshock upon stepping down from a start platform onto a grid of electrifiable metal rods (FIGURE 3) (171,269,272,413,460), and the older, step-through model in which animals are initially placed in a usually well-lit V-shaped compartment with metal walls and step through an open door into a similar but larger compartment where the opposing walls and the floor can be electrified (290,321,322 Both have become classic, and both give basically the same results. A few scattered laboratories have used two-trial or multiple-trial IA, with no real advantage over the more usual one-trial task.…”
Section: Lessons From One-trial Inhibitory Avoidance Learningmentioning
confidence: 99%
“…IA is by far the one in which more biochemical and pharmacological studies of memory consolidation in mammalian hippocampus in awake, behaving animals were carried out (70,72,73,105,116,183,208,264,265,267,271,272,400,401,403,405,413,563,657). Contextual and tone-conditioned fear and the LA or BLA come a distant second; Maren (379) commented on results of his own laboratory that suggest a specific role for the BLA in fear conditioning.…”
Section: Lessons From One-trial Inhibitory Avoidance Learningmentioning
confidence: 99%